Pancasila sebagai Dasar Hukum Tata Negara di Indonesia: Implikasi dan Implementasi: Pancasila as the Basis for Constitutional Law in Indonesia: Implications and Implementation - Ahmad Muhammad Mustain Nasoha; Mohammad Fanny Amrulloh; Ashfiya Nur Atqiya; Ahmad Tajun Nafi; Alayka Alvianto; Naufal Farid Geovani (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Pancasila as the foundation of the Indonesian state plays a key role in building a legal order that reflects the noble values of the nation. As the basis of constitutional law, Pancasila is not only an ideological symbol, but also a normative foundation that influences legislation, government systems, and national policy-making. This article aims to analyze the philosophical and juridical implications of Pancasila as the basis of law in Indonesia’s constitutional system and outline the application of its values in a dynamic legal context. Through a comprehensive literature review approach, the article identifies how Pancasila influences policy formation, law implementation and creates a balance between national stability and the principles of social justice, humanity and democracy. It also examines the challenges and constraints in implementing Pancasila values amidst socio-political dynamics as well as the need for legal reforms that are in line with changing times. Thus, this discussion provides insight into the continuing relevance of Pancasila in shaping a just and democratic legal framework to realize the ideals of the nation.